2019
DOI: 10.1038/s42003-019-0526-z
|View full text |Cite
|
Sign up to set email alerts
|

Ability of prebiotic polysaccharides to activate a HIF1α-antimicrobial peptide axis determines liver injury risk in zebrafish

Abstract: Natural polysaccharides have received much attention for their ability to ameliorate hepatic steatosis induced by high-fat diet. However, the potential risks of their use have been less investigated. Here, we show that the exopolysaccharides (EPS) from Lactobacillus rhamnosus GG (LGG) and L. casei BL23 reduce hepatic steatosis in zebrafish fed a high-fat diet, while BL23 EPS, but not LGG EPS, induce liver inflammation and injury. This is due to the fact that BL23 E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 74 publications
(92 reference statements)
1
44
0
Order By: Relevance
“…Galactose is the predominant sugar residue in SBM, arabinose in RSM, and xylose in SFM 83 . As recently described in zebrafish 84 , and extensively in mice and humans (reviewed in 85 ), different polysaccharides, including different NSP, have different effects on gut microbiota. Some contribute to the maintenance of gut microbial homeostasis, while others potentiate gut dysbiosis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Galactose is the predominant sugar residue in SBM, arabinose in RSM, and xylose in SFM 83 . As recently described in zebrafish 84 , and extensively in mice and humans (reviewed in 85 ), different polysaccharides, including different NSP, have different effects on gut microbiota. Some contribute to the maintenance of gut microbial homeostasis, while others potentiate gut dysbiosis.…”
Section: Discussionmentioning
confidence: 85%
“…Some contribute to the maintenance of gut microbial homeostasis, while others potentiate gut dysbiosis. This microbiota modulation is dependent on the polysaccharide structure, its fermentation by the gut bacteria and its direct interaction with the gut epithelium and mucus, which ultimately might result in physiological and inflammatory imbalances [83][84][85] . Although carbohydrates-metabolism has been exhaustively studied in different microorganisms, including gut ones, and there is enough genomic information (both from individual microorganisms and metagenomics studies) confirming that gut microorganisms possess the necessary enzymatic tools to metabolize different NSPs, it is not known which of these organisms are indeed capable of such metabolizing jobs within the complex context of natural gut communities and if metabolic pathways, capabilities and preferences determined in vitro will be replicated inside the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has illustrated that the activation of HIF-1 α resulted in the elevated expression of cathelicidins in order to inhibit gastrointestinal colonization of fungi ( 15 ). Recently, it was reported that the activation of intestinal HIF-1 α boosted local AMP expression to facilitate microbial homeostasis in zebrafish ( 51 ). Nevertheless, our result showed that the gene expression of turbot hepcidin in HKMs was not increased by SCFA treatment (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Although bacterial composition may be altered by endogenous and exogenous factors such as diet, age, genetics, sex, captivity, tissue and environmental conditions, the dominant species in specific organs are often consistent. [19][20][21][22][23][24][25] Previous studies have demonstrated that the microbial communities of teleost fish vary depending on the tissues they inhabit. 11,18,26 Additionally, new discoveries have been made in recent years regarding fish mucosal microbiota.…”
Section: Crob I Ome Comp Os Iti On Of Teleos T Mucosamentioning
confidence: 99%